Sedation of xylazine and lignocaine with adrenaline and bupivacaine for umbilical surgery in calves - Sarker, NC; Hashim, MA; Ray, BP; Sarker, SK (Journal of Bio-Science, 2011)
Context: The use of sedatives in veterinary practice is indispensable as they help in overcoming resistance of the animal during examination, maintaining depth of anaesthesia, reducing the dose of anaesthetic agent and increasing the margin of safety. Thus, action of some sedatives and local analgesics in various regional anaesthesia in calves and their evaluation in respect of doses are of great significance. The approximation of dose rate of available sedatives in calves may be helpful for the practitioners. Objectives: To determine the general effect of clinically useful dose of the sedatives produced by xylazine and lignocaine with adrenaline and bupivacaine for umbilical surgery in calves. Materials and Methods: The experiment was performed on 20 affected with umbilical hernia, 6 were indigenous (local) and 14 were crossbred. They were divided into 4 groups and each group included 5 calves. Groupp A was sedated with xylazine hydrochloride and 2% lignocaine hydrochloride; Group B with xylazine hydrochloride followed by 0.5% bupivcaine hydrochloride; Group C with diazepam followed by 2% lignocaine hydrochloride; and Group D diazepam followed by 0.5% bupivacaine. Respiratory rate, heart rate and rectal temperature were recorded before administration of sedatives and at 15, 30, 45, 60 minutes after sedation and local analgesia. Results: Heart rate and respiration rate significantly (p<0.01) decreased during sedation with xylazine hydrochloride plus 2% lignocaine hydrochloride or 0.5% bupivacaine hydrochloride. A significantly decreased (p<0.01) heart rate and respiration rate also found during sedation with diazepam plus 2% lignocaine hydrochloride or 0.5% bupivacaine hydrochloride. Duration of analgesia was longer with 0.5 % bupivacaine hydrochloride (55.88 ± 1.58 min in Group B and 48±11.25 min in Group D) compared to 2% lignocaine hydrochloride (39.60 ± 5.77 min in Group A and 43.6 ± 5.81 min in Group C). Xylazine hydrochloride showed short onset and long duration of sedation compared to diazepam. Conclusion: For herniorraphy, xylazine hydrochloride can be used as a better sedative while 0.5 % bupivacaine hydrochloride can be used as a local analgesic for longer duration of action. Keywords: Xylazine; lignocaine; diazepam; sedation; analgesia DOI: http://dx.doi.org/10.3329/jbs.v18i0.8789 JBS 2010; 18(0): 134-139